1973
DOI: 10.1084/jem.138.6.1564
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Hageman Factor in Solid and Fluid Phases

Abstract: The activation of Hageman factor results from its exposure to various insoluble particles having negative charges on their surfaces, such as glass, kaolin, extracellular membranes, etc., and to enzymes such as trypsin in solution. We have currently found that activation of Hageman factor by kaolin is highly inefficient in the presence of plasma, only a small percentage of the Hageman factor being utilized in the reaction (1). This led to the speculation that important soluble activators may exist in plasma tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
2

Year Published

1975
1975
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(158 citation statements)
references
References 15 publications
3
153
2
Order By: Relevance
“…Thus, it is considered that the kallikrein activity in plasma mainly reflects the micromotion of the prosthesis in the radiolucent zone. Exposure of collagen fibres in fibrous tissue of the radiolucent zone (DeLee & Charnley 1976), resulting from micromotion, may also participate as an inducer in contact activation (Cochrane et al 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is considered that the kallikrein activity in plasma mainly reflects the micromotion of the prosthesis in the radiolucent zone. Exposure of collagen fibres in fibrous tissue of the radiolucent zone (DeLee & Charnley 1976), resulting from micromotion, may also participate as an inducer in contact activation (Cochrane et al 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, damage to the EC layer might expose subcellular structures with a sufficient density of negative charges to facilitate assembly of the surfacebound HF-high Mr kininogen-Factor XI-prekallikrein complexes similar to the one demonstrated for kaolin (12,39,40). Under these circumstances, the EC enzyme could initiate HF cleavage, an essential step for the reciprocal activation between HF and prekallikrein (41). This may be one mechanism by which HF is activated in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Higher concentrations of prekallikrein levels may suggest the onset of renal abnormalities. In fact, high plasma prekallikrein levels have been documented in type 1 diabetic patients [27]. These investigators suggested that increased plasma prekallikrein level could be a risk factor for hypertension and nephropathy in type 1 diabetes.…”
Section: The Bradykinin System and Diabetesmentioning
confidence: 96%
“…Tissue kallikrein has also been reported to be present in plasma [22,23] Plasma kallikrein preferentially acts on high molecular weight kininogen substrate to release BK. BK promotes both cardiovascular and renal functions, for example, vasodilation, naturesis and diuresis [24,25] BK is rapidly (< 15 sec) inactivated by circulating kinases [26] BK acts on B1receptor (B1R) and B2 receptor (B2R) [27] to elicit physiological and pharmacological actions. It has been shown previously that type 1 diabetic patients are at a risk of developing nephropathy, having increased renal tissue kallikrein and BK levels [28].…”
Section: The Bradykinin System and Diabetesmentioning
confidence: 99%